Educação de jovens e adultos: um olhar sobre o governo Jair Messias Bolsonaro - Nakadaki, Vitória Evelin Pignatari (2020)
The Education of Youths and Adults - EJA, in the contemporary world, is notorious as a modality of teaching basic education, claimed by the Brazilian jurisdiction as a fundamental right, repairing - of an emerging trend - the historical-social debt to those who have been denied their right to education in the own age. Such a situation emerges in the current compensatory, equalizing and qualifying character of public policies, whose effectiveness in combating illiteracy and its setbacks has, over the past decades, been inept, flawed. In view of this, it was pertinent to ask, due to the object of the present research, “what initiatives, at the level of public policies of the Jair Messias Bolsonaro Government, were taken for the Education of Youths and Adults in Brazil? ”. In order to elucidate the issue, we opted for the development of exploratory research of a qualitative nature (MINAYO, 2002), by means of bibliographic and documentary analysis, using specialized literature of current research and national norms. It was found, after observing historical and current indications, regarding the path of consolidation of the modality - from the colonial to the republican period, that contemporary public policies aimed at EJA, before and during a period of historical exceptionality posed by the Covidean pandemic 19, have configured public neglect and emergency actions, sometimes palliative, sometimes insufficient, which has substantially affected the access and participation of students, considering, among other factors, the dismantling of institutional structures and the reorganization of the school calendar under circumstances of social isolation and sudden adaptation to the unusual demand for remote, or non-face-to-face teaching, whose ordering in the public educational system proved to be incipient.